Le rendement à tout prix. Produire et gérer le coliving bruxellois en contexte de financiarisation - Charlotte Casier (Métropoles)
The article examines how the increasing financialisation of the housing market is materialised in modes of production and management of real estate geared towards high and quick yields. Using mainly qualitative methods, it takes as a case study the Brussels coliving sector - a real estate niche in which private companies rent out furnished rooms in the same building, along with common areas and services, to a clientele of young expatriates. By documenting the strategies of these management companies in Brussels, the paper sheds light on the modalities of the financialisation of a small but growing proportion of the residential real estate sector. This is manifested in the densification of space, the shortening of production times and the reduction of management work. The article also shows how real estate industry adapts its products to the constraints of the local territory in order to take advantage of them.